2020
DOI: 10.1016/j.msard.2020.102141
|View full text |Cite
|
Sign up to set email alerts
|

Alemtuzumab-induced simultaneous onset of autoimmune haemolytic anaemia, alveolar haemorrhage, nephropathy, and stroke: A case report

Abstract: Background: Alemtuzumab is a humanized anti-CD 52 monoclonal antibody approved as a disease-modifying therapy for active relapsing-remitting Multiple Sclerosis (MS). Alemtuzumab has been associated with several adverse effects, including infusion-associated reactions, infections, acquired autoimmune diseases, and malignancies. Case presentation: We report a case of Alemtuzumab-induced simultaneous onset of autoimmune haemolytic anaemia, alveolar haemorrhage, nephropathy and stroke in a 52-year-old man that occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Fifty-three case reports and 10 case series were evaluated using the risk of bias assessment tool. Regarding case reports, 8 studies ( 33 , 37 , 42 , 58 , 67 , 70 , 75 , 81 ) had the highest methodological quality, together with 3 other studies ( 30 , 43 , 56 ) that similarly reported high quality information. For the remaining case reports, the risk of bias evaluation revealed mainly the lack of data on patients’ race and patients’ history presented as timeline.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-three case reports and 10 case series were evaluated using the risk of bias assessment tool. Regarding case reports, 8 studies ( 33 , 37 , 42 , 58 , 67 , 70 , 75 , 81 ) had the highest methodological quality, together with 3 other studies ( 30 , 43 , 56 ) that similarly reported high quality information. For the remaining case reports, the risk of bias evaluation revealed mainly the lack of data on patients’ race and patients’ history presented as timeline.…”
Section: Resultsmentioning
confidence: 99%
“…The objective of this investigation was to ascertain the factors that contribute to the hematological irregularities commonly observed in association with these therapies. Several reports have surfaced regarding the incidence of stroke and suboptimal neurological outcomes among patients diagnosed with MS who have undergone alemtuzumab therapy for a minimum of two doses at least 66,67 . They were perhaps linked to hypertension, hence MS patients on alemtuzumab must have frequent arterial pressure monitoring, with special attention paid to increases in systolic BP of more than 20 mmHg, or 20%.…”
Section: Discussionmentioning
confidence: 99%
“…According to existing literature, treatment with subcutaneous interferon beta 1a (IFN-β1a) does not increase the risk of stroke in patients with MS. 31 Muhannad et al reported a case of alemtuzumab-induced simultaneous onset of autoimmune hemolytic anemia, alveolar hemorrhage, nephropathy, and stroke in a 52-year-old man that occurred 8 months after treatment initiation. 32 On the other hand, dimethyl fumarate (DMF) is hypothesized to provide clinical benefit to MS patients in case of ischemic stroke. 33 …”
Section: Discussionmentioning
confidence: 99%